Modeling of the stress-strain state in the earthquake epicenter area (Kumamoto Earthquake, Japan), 16.04.2016 M 7.3 - V. N. Morozov; A. I. Manevich (Известия высших учебных заведений: Геология и разведка)
On the 16th of April, 2016, a strong earthquake with M 7,3 occurred in the Kumamoto prefecture (Kyushu, Japan). This earthquake is the strongest in the last 30 years in this area. For a day before the main shock, two foreshocks with M 6,4 were registered. For seven days after the main shock, aftershocks activity spread to the north-east and south-west, most of the hypocentres of the aftershocks with M 6,4 were localized within the seismogenic layer in the depth interval from 5 to 10 km. The authors have modeled a stress-strain state (SSS) of the epicentral area be fore the earthquake and after it (after the formation of the main fault). For this purpose, a software package is used, that allows 2-D formulation (plane strain condition), for modeling SSS block heterogeneous geological environment, disrupted by a system of tectonic faults. The faults are modeled in the form of extended zones of the dispersed geomaterial, which elastic modulus are significantly lower than the elastic modulus of the environmental media. A structural-tectonic scheme of the Kumamoto earthquake area is used. An analysis of the results of SSS modeling has been done for the area 30x40 km before and after the earthquake. It is shown that the area and magnitude of the stress intensity in anomalous zones are the predictive signs of the location and intensity of a possible strong crustal earthquake, and the vector of the rapid decrease in the potential energy of deformation could be a guide for the most probable direction of tectonic rupture during a crustal earthquake. The results received can be useful in a deterministic approach to seismic hazard assessment and carrying out the geophysical observations focused on the forecast of the strong crustal earthquakes in the continental areas.